Comparison between prolotherapy using 25% dextrose versus extracorporeal shock wave therapy in the management of pain and improvement of functional outcome in patients suffering from chronic lateral epicondylitis: a randomized controlled trial - Deb, Debasish; Singh, Akoijam Joy; Singh, Naorem Bimol; Singh, Yumnam Nandabir; Das, Rakesh; Meethal, Sahanavas Anoth; Deb, Suman (International Journal of Research in Medical Sciences, 2020)
Background: Lateral epicondylitis is a tendinopathy characterized by pain around the lateral aspect of the elbow occuring more frequently in nonathletes than athletes significantly affecting the patient’s life in terms of the quantity and quality of work done. In resistant cases of tennis elbow, a number of treatment options have been tried including extracorporeal shockwave therapy, autologous blood injections and surgery as last resort but none of them has proved to be superior over another. Recent studies show that 25% dextrose prolotherapy which induces an inflammatory reaction at site of administration would be a better treatment option in resistant cases. Methods: A prospective randomized controlled trial was done in Department of Physical Medicine & Rehabilitation, Regional Institute of Medical Sciences, Imphal to compare the effectiveness of 25% dextrose prolotherapy injection and extracorporeal shockwave therapy in management of pain and improvement of functional outcome in patients suffering from chronic lateral epicondylitis. Results: The outcome variables VAS for pain and Grip strength for function were measured at baseline, 1 month, 3 months and 6months. Data collected were analysed using SPSS version 21. For analytical purpose, description statistics like mean and standard deviation were used. Statistical tests like t-test, Chi square test, Fisher’s exact test were used for intra group and inter group analysis. P-value <0.05 was taken as significant. In study group 2ml of 25% dextrose mixed with 2% lignocaine (0.5ml) was given to the affected lateral epicondyle. In control group, weekly sessions of single sitting ESWT was given to the lateral epicondyle for 3 consecutive weeks. In the follow up assessment at 1 month, 3 months and 6 months, there was significant improvement in mean score of VAS and Grip Strength scores in both the groups (p<0.05). When both the groups were compared with each other, study group showed a better improvement and was found to be significantly more effective than shockwave therapy group in reducing pain and improvement of functional outcome in chronic lateral epicondylitis (p = 0.001). Conclusions: Prolotherapy may be considered as a novel alternative conservative management before opting for surgery in resistant cases of lateral epicondylitis.